Impact of energy efficiency and sharing economy on the achievement of sustainable economic development: New evidences from China - Fangyu Ye; Li Yi; Peilin Liu (Journal of Innovation & Knowledge (JIK), 2023)
Recently, energy efficiency and the sharing economy have become significant factors for sustainable economic development (SED), which require the attention of researchers and policymakers. Thus, the present research investigates the impact of energy efficiency and the sharing economy on SED in China. Secondary data is used covering the period from 1991 to 2020. The study runs the augmented Dickey-Fuller (ADF) test to check the unit root and the quantile autoregressive distributed lag (QARDL) model to investigate the linkages amongst the variables. The results indicate that efficient energy use, sharing economy users, sharing economy values, population growth, urbanization and industrialization have positive linkages with SED in China. This study guides policymakers developing policies related to the achievement of SED using efficient energy and a valuable sharing economy.
Keywords: L86; Q01; Q49; 650; Efficient energy use; Industrialization; Population growth; Sharing economy; Sustainable economic development; Urbanization